CYTOTOXIC ACTIVITY OF DENDRITIC CELLS AGAINST ACTIVATED CD4+ AND CD8+T-LYMPHOCYTES IN THE CULTURE IN VITRO - T. V. Tyrinova; O. Yu. Leplina; M. A. Tihonova; A. A. Ostanin; E. R. Chernykh (Acta Biomedica Scientifica)
The aim of the present study was a comparative assessment of the cytotoxic activity of IFNα-induced dendritic cells (IFN-DCs) and IL-4-induced DCs (IL4-DCs) against allo-MLC- activated CD4+ and CD8+T-lymphocytes. It was shown the level of AnnexinV+/PI- cells corresponding to early apoptosis among CD4+T-lymphocytes was lower in cultures with IFN-DCs compared with IL4-DCs. At the same time the relative number of AnnexinV+/ PI+ cells (late phase of apoptosis/necrosis) among CD4+T-lymphocytes activated by allogenic IFN-DCs and IL4-DCs increased in an equal degree. It was demonstrated that IFN-DCs possesed similar ability to induce apoptosis of CD3+CD8+T-lymphocytes.